TINJAUAN HUKUM TERHADAP BATASAN UMUR DEWASA SEBAGAI PEMEGANG SERTIFIKAT HAK ATAS TANAH - Idfi Yava Dwilestari; andi Risma; Muhammad Ilyas (Qawanin Jurnal Ilmu Hukum, 2021)
ABSTRAC This study aims to determine the regulation of the age limit for adults as holders of land rights certificates and to find out the legal consequences if someone wants to make a certificate of land rights even though they are not old enough. This research uses a normative research method using a law approach and a case study approach. Then the data obtained were analyzed descriptively qualitatively so as to reveal the expected resultsand conclusions on the problem. The results of this study indicate that: Thediversity of regulations regarding the adult age limit in the law makes BPN issue a new regulation, namely the Ministerial Circular which has been regulated in the Circular of the Minister of Agrarian Affairs/Head of the National Land Agency Number 4/SE/I/2015, namely the adult age in land service framework is 18 years or already married. The Circular is contrary to Article 330 BW which regulates the adult age of 21 years. The legal consequences that occur in the making of land rights certificates that do not meet the requirements of adult age are administrative defects but are not canceled but the certificate cannot be used until it is of sufficient age and the certificate will be held by an appointed guardian. Recommendations for this research: it is hoped that with the Circular Letter of the Minister of Agrarian Affairs/Head of the National Land Agency Number 4/SE/I/2015 regarding adult age, it can provide uniformity regarding the adult age limitin the context of land services throughout the National Land Agency in Indonesia. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaturan batasan umur dewasa sebagai pemegang sertifikat hak atas tanah dan untuk mengetahui akibat hukum apabila seseorang ingin membuat sertifikat hak atas tanah padahal belum cukup umur. Penelitian ini menggunakan metode penelitian Normatif dengan menggunakan metode pendekatan undang-undang dan pendekatan studi kasus. Kemudian data yang diperolehdianalisis secara deskriptif kualitatif sehingga mengungkapkan hasil yang diharapkan dan kesimpulan atas permasalahan. Hasil penelitian ini menunjukkan bahwa: Pengaturan mengenai batas usia dewasa telah diatur dalam Surat Edaran Menteri Agraria/ Kepala Badan Pertanahan Nasional Nomor 4/SE/I/2015 yaitu usia dewasa dalam rangka pelayanan pertanahan adalah 18 tahun atau sudah menikah. Surat Edarantersebut bertentangan dengan Pasal 330 BW yang mengatur umur dewasa yaitu21 tahun. Akibat hukum yang terjadi dalam pembuatan sertifikat hak atas tanah yang belum memenuhi syarat cukup umur dewasa tersebut yaitu cacat administrasi tetapi tidak dibatalkan akan tetapi sertifikat tersebut tidak bisa digunakan sampai usianya mencukupi dan sertifikatnya akan dipegang oleh wali yang telah ditetapkan. Rekomendasi penelitian ini : diharapkan dengan adanya Surat Edaran Menteri Agraria/ Kepala Badan Pertanahan Nasional Nomor 4/SE/I/2015 tentang usia dewasa, bisamemberikan keseragaman terkait batasan umur dewasa dalam rangka pelayanan pertanahan di seluruh Badan Pertanahan Nasional yang ada di Indonesia.